Optimizing Network Performance Through the Integration of SDN (Software-Defined Networking) Systems in Universities - Sabrina, Nabila Khalilah; Made Suliana, I; Rahman , Sultan Nur; Pepriyani , Nor Lintang; Royd , Ivan Cavanneva (LPPM Universitas Sari Mulia, 2025)
The advancement of information technology in higher education requires a reliable network infrastructure to support academic, research, and administrative activities. This study aims to design a computer network infrastructure for Building E at Sari Mulia University using the Waterfall model. The research includes needs analysis, system design, simulation-based implementation with Cisco Packet Tracer, and performance evaluation. The needs analysis identifies user requirements, devices, and applications to ensure the network supports high-speed internet, central server connectivity, and e-learning systems. The proposed design uses a hierarchical topology with core, distribution, and access layers, along with VLANs to optimize data traffic and reduce congestion. The simulation results showed that the network design performed as expected, with a success rate of 90-95%. However, improvements are needed, particularly in the wireless network (WLAN), where coverage was insufficient in certain areas due to limited access points and physical barriers. In conclusion, the network design effectively supports the university's academic and administrative needs, with room for growth and future technology integration.